ChemInform Abstract: Sustainable Synthesis of 2‐Arylbenzoxazoles over a Cobalt‐Based Nanocomposite Catalyst. Issue 45 (October 2016) - He, Jian; Lin, Fu; Yang, Xufang; Wang, Di; Tan, Xiaohua; Zhang, Shujun
Abstract: The new cobalt‐based heterogeneous catalyst is prepared by adsorbing in situ produced nitrogen‐ligated cobalt(II) acetate complexes on commercially available SiO2 and subsequent pyrolysis at 800 °C for 2 h under N2 atmosphere.